(untitled) (Bangladesh Journal of Agricultural Research, 2016)
Nine morphological and physiological traits were taken to assess genetic parameters, association between the traits and grain yield and partition correlation of yield with other traits, which were purposefully considered as the important strategy for the investigation. Therefore, the main objective of the present investigation was to find out suitable morpho-physiological traits that could be invariably used for the yield improvement of spring wheat grown under drought stress condition. Thirty wheat diverse genotypes were evaluated under drought stress field condition in Alpha Lattice Design with three replications. The study revealed wide range of variability and high broad sense heritability for most of the traits (early ground coverage, canopy temperature, peduncle length, relative water content, number of spikes per m2 and 1,000-grain weight). Genetic advance in percent of mean suggested that there is enough scope for further improvement of genotypes for the characters studied. Correlation studies exhibited that grain yield was positively and significantly associated with early ground coverage and 1000-grain weight. The path analysis also revealed a maximum direct effect on grain yield contributed by 1000-grain weight. Early ground coverage and 1000-grain weight had a significant and spikes per m2 had positive indirect effect on grain yield. Therefore, these three traits were found to be most important for wheat breeding under drought stress. As these traits can be evaluated quickly and easily, hence breeders can choose these traits for selecting potential wheat genotypes for further breeding programs. Bangladesh J. Agril. Res. 41(2): 235-250, June 2016